(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Annotation: The article is devoted to the issue of adaptation of disabled children in the modern world. The work reflects the state of the problem of childhood disability. The basic concepts on the topic discussed in the article are given, the situation with the prevalence of disability in Russia is described, and the features of the adaptation process of children with disabilities are characterized. The importance of participation in the process of adaptation of families and educational institutions of all levels is described.